50 rules for teenagers. 1 - Na, Ye-Ri.; Eggleston, Trisha (Houston, Tex. : ADV Manga, 2004)
Fifteen-year-old Mi-Roo Yoo, trying to fill in for her mostly-missing mother, struggles to balance the demands of home and school and keep her conniving twin brother, Ma-Roo, under control.
Translated from the Korean.
School Library Journal.
Voice of Youth Advocates (V.O.Y.A.).
Adult
Keywords: Family -- Fiction; Responsibility -- Fiction; Teenagers -- Fiction; Twins -- Fiction; Comic books, strips, etc; Family life -- Fiction; Responsibility -- Fiction; Teenagers -- Fiction; Twins -- Fiction; Domestic fiction; Graphic novels